A modulator of the low-voltage-activated T-type calcium channel that reverses HIV glycoprotein 120-, paclitaxel-, and spinal nerve ligation-induced peripheral neuropathies. Issue 11 (November 2020) - Cai, Song; Tuohy, Peter; Ma, Chunlong; Kitamura, Naoya; Gomez, Kimberly; Zhou, Yuan; Ran, Dongzhi; Bellampalli, Shreya Sai; Yu, Jie; Luo, Shizhen; Dorame, Angie; Yen Ngan Pham, Nancy; et al.
Abstract : Abstract: The voltage-gated calcium channels CaV3.1–3.3 constitute the T-type subfamily, whose dysfunctions are associated with epilepsy, psychiatric disorders, and chronic pain. The unique properties of low-voltage-activation, faster inactivation, and slower deactivation of these channels support their role in modulation of cellular excitability and low-threshold firing. Thus, selective T-type calcium channel antagonists are highly sought after. Here, we explored Ugi-azide multicomponent reaction products to identify compounds targeting T-type calcium channel. Of the 46 compounds tested, an analog of benzimidazolonepiperidine—5bk (1-1-[(R)-1-[(1S)-1-phenylethyl]-1H-1, 2, 3, 4-tetrazol-5-yl(thiophen-3-yl)methyl]piperidin-4-yl-2, 3-dihydro-1H-1, 3-benzodiazol-2-one) modulated depolarization-induced calcium influx in rat sensory neurons. Modulation of T-type calcium channels by 5bk was further confirmed in whole-cell patch clamp assays in dorsal root ganglion (DRG) neurons, where pharmacological isolation of T-type currents led to a time- and concentration-dependent regulation with a low micromolar IC50 . Lack of an acute effect of 5bk argues against a direct action on T-type channels. Genetic knockdown revealed CaV3.2 to be the isoform preferentially modulated by 5bk. High voltage-gated calcium, as well as tetrodotoxin-sensitive and -resistant sodium, channels were unaffected by 5bk. 5bk inhibited spontaneous excitatory postsynaptic currents and depolarization-evoked release of calcitonin gene-related peptide from lumbar spinal cord slices. Notably, 5bk did not bind human mu, delta, or kappa opioid receptors. 5bk reversed mechanical allodynia in rat models of HIV-associated neuropathy, chemotherapy-induced peripheral neuropathy, and spinal nerve ligation-induced neuropathy, without effects on locomotion or anxiety. Thus, 5bk represents a novel T-type modulator that could be used to develop nonaddictive pain therapeutics. Abstract : Supplemental Digital Content is Available in the Text.A screening campaign identified a novel CaV3.2 T-type calcium channel inhibitor with broad antinociceptive potential and without action on opioid receptors.